Emotion in social life : the lost heart of society - Layder, Derek (SAGE, 2004)
Interpersonal relations between real people are the essential heart of society but it is a 'heart' that has for too long been overlooked in social and psychological analysis. The book outlines a new way of thinking about control and power in everyday life.